Teen Titans. Beast Boy loves Raven - Garcia, Kami (DC Comics, 2021)
Raven Roth and Garfield Logan cross paths when they both head to Nashville to meet Slade Wilson, a mysterious man who says he has the answers to all their questions. As they wait for Slade, the two spend more time together and slowly become friends and possibly something more. But when they are kidnapped by Slade, Raven's foster sister Max and Damien Wayne team up to help break them out of a mysterious facility.